Exploring Javanese Accent Influence: University Students' Perceptions, Motivation, and Coping Strategies in English Pronunciation - Athifah Oktavia Rahmadini; Meryanti Meryanti; Silvina Chairunnisa; Neneng Sunengsih (Universitas Cokroaminoto Palopo, 2026)
The influence of Javanese accents on the pronunciation of English by Indonesia students is still limited. Therefore, the purpose of this research is to investigate how Javanese accents influence students' pronunciation of English and to understand their perceptions of the challenges they face in improving their pronunciation. We employed a qualitative method, utilizing semi-structured interviews, with approximately eight students from various universities in Indonesia who speak Javanese as their mother tongue participating. The collected data will be analyzed by topic to find different patterns and topics related to the influence of accents on English pronunciation. The expected result of this research is to provide a deeper understanding of how Javanese accents influence students ' pronunciation of English, especially in phonetic aspects. The results of this research are also expected to make a significant contribution to pronunciation teaching strategies, enabling teachers to more effectively address the common difficulties faced by students from a Javanese background.